2022
DOI: 10.1002/smll.202105988
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Activated Nanofibrous Membrane with Self‐Rechargeable Antibacterial Function for Stubborn Infected Cutaneous Regeneration

Abstract: For quick disinfection treatment, phototherapy, including photothermal therapy and photodynamic therapy, has emerged as a promising alternative to conventional methods. However, the bactericidal effect of phototherapy, which only works upon light, is short‐lived. The remaining bacteria in situ may repopulate when the irradiation of light is withdrawn. To address this refractory concern, an antibacterial fibrous membrane consisting of electrospun poly (polycaprolactone) scaffolds and polydopamine (pDA) coated M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Once the intruders are not cleared, the immune response are over-reactive, leading to damage the tissue 67 . Thereby, bacteria elimination is more critical for the healing process 68 , 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Once the intruders are not cleared, the immune response are over-reactive, leading to damage the tissue 67 . Thereby, bacteria elimination is more critical for the healing process 68 , 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Skin, serving as the largest organ and the first line of body defense, maintains stability in the interior environment when faced with external threats [ 147 ]. Nonetheless, infected dermis wounds may cause pain, amputations or even death and have emerged as one of the severest threats to global health security [ 27 ]. Sponge, bandages, and gauze are the most routinely used wound dressings, and they possess ordinary functions by forming a physical parclose or assimilating exudate.…”
Section: Applications Of Mxenes In Antibacterial and Related Fieldsmentioning
confidence: 99%
“…MXenes@PVA hydrogel exhibited high toughness, anisotropy, and antimicrobial properties, hinting it could be an attractive dressing for antibacterial wound healing. In addition to the above composites, Ti 3 C 2 T x /Ag 3 PO 4 [27], Ti 3 C 2 T x /MoS 2 [149], Ti 3 C 2 T x / Bi 2 S 3 [16], Ti 3 C 2 T x /Ag [41], and Nb 2 C [150] have all shown promising prospects for in vivo wound healing; the research progress could be found in Table 4.…”
Section: In Vivo Antibacterial Applicationsmentioning
confidence: 99%
See 2 more Smart Citations